Cancellation of request for tender of HVAC system, lift & escalators, fire detection & protection, generator, substation, Busbar Trunking (BBT), photovoltaic solar system, Main Distribution Board (MDB) and Distribution Board - Brac University (Brac University, 2023)
This record consists of general correspondence regarding cancellation of request for tender of HVAC system, lift & escalators, fire detection & protection, generator, substation, Busbar Trunking (BBT), photovoltaic solar system, Main Distribution Board (MDB) and Distribution Board of BRAC University new campus project.